Urban form, water and green spaces: Towards an integrated aproach of resilient urban systems - Marat-Mendes, T. (2021)
Urban planning has been engaged for a long time with one issue: how to plan the expansion of cities. The main aim of this paper is to determine why have such theory emerged and why it is not working any longer. In addition, it reflects on what does urban metabolism has to do with the urban form arrangements and urban infrastructures (water and green spaces in particular). This reflection is based on an examination of the urban planning options taken for Lisbon and its region during twentieth century, in particular in what relates to urban form, water infrastructures and green spaces. Finally, this presentation argues that to transform our cities into more resilient places it is important that Urban Form should be recognized as a strategic tool to transform the current metabolic functioning of our cities. However that will only be possible when a full understanding of the role Urban Form, which integrates also Green Spaces and water infrastructures, within the urban system metabolism is recognized by society itself.